PENGARUH BRAND UNDERSTANDING, BRAND INFLUENCE DAN BRAND CREDIBILITY TERHADAP MINAT ELECTRONIC WORD OF MOUTH DI MEDAN (Studi pada Mahasiswa FEB UnHar Medan) - Annisha Suvero Suyar; Ani Murwani Muhar (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2021)
This study aims to determine the effect of brand understanding, brand influence and brand credibility on the selection of private universities in electronic word of mouth, either partially or simultaneously. The population in this study was 100 with a sample of 100 respondents using a sampling technique, namely probability sampling. The analysis technique used is multiple linear regression. The results showed that brand understanding had no effect on the selection of private universities in electronic word of mouth, brand influence had no effect on the selection of private universities in electronic word of mouth, brand credibility had a positive and significant effect on the selection of private universities in electronic word of mouth. , brand understanding, brand influence and brand credibility have a positive and significant effect on the selection of private universities in electronic word of mouth and the selection of private universities in electronic word of mouth (y) is influenced by X1 (brand understanding), X2 (brand influence), and X3 (brand credibility) of 10.7%